Molecular interactions of Andrographis paniculata Burm. f. Active Compound with Nuclear Receptor (CAR and PXR): An In Silico Assessment Approach - Agung Endro Nugroho; Arief Nurrochmad; Endang Lukitaningsih; Elza Sundhani (Universitas Gadjah Mada, 2022)
The study aims to analyze the potential Herb-Drug Interactions (HDIs) of the chemical compound in Andrographis paniculate Burm. f. against Constitutive Androstane Receptor (CAR) and Pregnane X Receptor (PXR). The 1XVP and 1SKX obtained from the Protein Data Bank (PDB) were used as the targeted protein. The molecular docking analysis was done using the Molecular Operating Environment (MOE) and molecular dynamics simulation using Gromacs. The results of the docking analysis showed that 14-Deoxy-11,12-didehydroandrographolide had the strongest binding energy (1XVP-21.0998 Å) with the Arene-H binding type on Tyr326 and Andrographidine A had the strongest binding energy (1SKX-24.7363 Å) with the Arene-H binding type on Trp299. While Andrographolide is the major component, it also has a high affinity for the two PDB IDs (1XVP-17.4044 Å and 1SKX-21.8881 Å). Based on the RMSD value, the radius of gyration (Rg), and MM/PBSA on molecular dynamic simulations, it shows that the ligand and protein complex as a whole can bind strongly to amino acid residues at the active site. The complex also has sufficient stability and good affinity. Therefore, this study can predict the mechanism in HDIs, especially in CYP 450 expression through the activation pathways of CAR and PXR receptors.